FROM PERIPHERAL TRADITION TO EPISTEMIC CORE: Rangkang in Acehnese Islamic Educational Thought - Amiruddin Amiruddin; Ismail Fahmi Arrauf Nasution; M. Anzaikhan; Yustizar Yustizar (State Islamic University North Sumatra, 2026)
Contemporary discourse on Islamic education in Aceh has predominantly centered on institutional reform and curricular adjustment, yet it has insufficiently addressed the deeper epistemic rupture underlying the crisis of adab, the erosion of pedagogical relationships, and the superficiality of learning processes. The historical marginalization of rangkang—often reduced to a merely descriptive artifact—reveals a conceptual void in understanding the foundational structure of Acehnese local pedagogy. This study reconstructs rangkang as a constitutive element of the Acehnese epistemic prototype through a qualitative historical–conceptual approach grounded in the analysis of manuscripts, colonial archives, classical texts, and contemporary scholarly works. The findings demonstrate that rangkang functioned as an integral epistemic infrastructure, integrating relational-humanistic pedagogy, dialogical and gradual (slow) learning, and the principle of adab qabl al-‘ilm in the formation of knowledge. Rather than a peripheral component, rangkang served as a structural nexus ensuring continuity between intellectual tradition, social order, and spiritual discipline. This study contributes to the scholarship on Islamic education by formulating rangkang as a local epistemic prototype that challenges institutionalist paradigms and offers a model of Islamic education that is tradition-rooted yet globally resonant.